Challenge and change in the information society (Facet, 2003)
The book has 5 parts that focuses on the change and challenge in the information society. Each chapter of this book is written by an expert and contributions are divided into five sections encompassing broad themes. Part 1 outlines theories of the information society; Part 2 discusses policy and organizational perspectives; Part 3 addresses the technological imperative; Part 4 considers the implications of the information society and the individual; and Part 5 examines professional issues. For anyone interested in examining the changing nature of the global information society.